A Heat Method of Extracting Myzus persicae Sulzer (Homoptera: Aphididae) from Potato Leaves. - Hussein, Mohd Yusof (1983)
A simple and rapid method of extracting the green peach aphid, Myzus persicae Sulzer from potato (Solanum tuberosum) leaves by heat was developed. In this method, each aphid-infested potato leaf was placed directly into a paper bag and sealed in the field itself, On arrival at the laboratory, the bags were heated in the oven at the specified temperature and duration. Four temperatures (40, 45, 50 and 55°C) and five durations of exposure (4, 8, 16, 32 and 64 minutes) were tested. The results showed that either the combinations of 50° C and 32 or 64 minutes or 55°C and 8 or 16 minutes exposure gave more or less the same high percentage of extraction (P>0.05 by LSD) without causing severe discoloration and burning of aphids. The method was found to be practical, simple and time-saving especially when a large number of leaves were involved during the peak infestation of aphids.